A Study of Interaction Patterns and Awareness Design Elements in a Massively Multiplayer Online Game. (1st January 2008) - Tang, Tiffany Y.; Man, Cheung Yiu; Hang, Chu Pok; Cheuk, Lam Shiu; Kwong, Chan Wai; Chi, Yiu Chung; Fai, Ho Ka; Kam, Sit
Abstract : Massively multiplayer online games (MMOGs) have been known to create rich and versatile social worlds for thousands of millions of players to participate. As such, various game elements and advance technologies such as artificial intelligence have been applied to encourage and facilitate social interactions in these online communities, the key to the success of MMOGs. However, there is a lack of studies addressing the usability of these elements in games. In this paper, we look into interaction patterns and awareness design elements that support the awareness in LastWorld and FairyLand . Experimental results obtained through both in-game experiences and player interviews reveal that not all awareness tools (e.g., an in-game map) have been fully exploited by players. In addition, those players who are aware of these tools are not satisfied with them. Our findings suggest that awareness-oriented tools/channels should be easy to interpret and rich in conveying "knowledge" so as to reduce players-cognitive overload. These findings of this research recommend considerations of early stage MMOG design.